Prevalance and Risk Factors of Diabetic Nephropathy in Type 2 Diabetes Patients at Pangsilathong Hospital, Kamphaeng Phet Province, Thailand - Pakapaiboon S (Journal of The Department of Medical Services, 2020)
Background: Diabetic nephropathy is the major cause of chronic kidney disease in type 2 diabetes patients. Objective: The aims of this study were to determine the prevalence and risk factors of diabetic nephropathy in type 2 diabetes patients at Pangsilathong Hospital. Method: The data of 1,216 type 2 diabetes patients were collected between 1 October 2018 and 30 June 2019. The statistics was used by Univariate logistic regression and Multivariate logistic regression for identifying risk factors of diabetic nephropathy in type 2 diabetes. Result: The finding showed that the prevalence of diabetic nephropathy in type 2 diabetes at Pangsilathong Hospital was 33.8%. After multivariate analysis of risk factors associated with diabetic nephropathy were Serum Creatinine >1.4 mg. /dl., Hemoglobin A1c >7%, Uncontrolled blood pressure (≥140/90 mmHg.), male, Triglyceride >200 mg. /dl. and eGFR <60 ml./min. Conclusion: Management of NCD clinic should be early detection for diabetic nephropathy and aggressive management of risk factors may be essential in preventing or delaying the progression to chronic kidney disease.